Investigating the effective factors of using mHealth apps for monitoring COVID-19 symptoms and contact tracing: A survey among Iranian citizens. (November 2021) - Rahimi, Rezvan; Khoundabi, Batoul; fathian, Akram
Highlights: Technology has played a key role in combating the COVID-19 pandemic. The use of mHealth apps depends on the cognitive and social factors of individuals. More than 60% of participants in this study mentioned "for protecting their health and that of their families" as the main reason for using COVID-19 mHealth apps.. The reasons given for not using COVID-19 mHealth apps were related to the issues of "security and privacy", "doubt in efficiency and usefulness". Abstract: Background and objectives: The use of mHealth applications depends on cognitive and social factors of individuals in different nations. This study aimed to identify the factors influencing the use of mHealth applications for both "contact-tracing" and "symptom-monitoring" of COVID-19 among Iranian citizens. Methods: A cross-sectional study with an online survey was conducted among Iranian citizens. Correlation calculation and multiple linear regression analysis were performed on the studied variables to find the effective factors. Results: A total of 1031 Iranian citizens over the age of 18 participated in this survey. A large percentage of the participants wanted to use the mHealth app to trace contacts of COVID-19 (74.5%) and the mHealth app to identify and monitor COVID-19 symptoms (74.0%). Gender, age, level of education, attitude towards technology, and fear of COVID-19 were among the factors that influenced the intention to use these two apps. The top reasons for using these apps were: "to keep myself and my family safe", "to control the spread of the coronavirus in general", and "to cooperate with healthcare professionals". The reasons given for not using these two apps were related to the issues of "security and privacy" and "doubt in efficiency and usefulness" of them. Conclusions: The study showed that many participants in this survey were interested in using the COVID-19 apps. Policies, regulations and procedures are needed to protect the privacy of individuals by ensuring data governance. Further investigation with a larger sample is suggested to generalize these results.